2021
DOI: 10.1007/s00300-021-02925-1
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and temporal diet variability of Adélie (Pygoscelis adeliae) and Emperor (Aptenodytes forsteri) Penguin: a multi tissue stable isotope analysis

Abstract: The Ross Sea, Antarctica, supports large populations of Emperor Penguin (Aptenodytes forsteri) and Adélie Penguin (Pygoscelis adeliae), two key meso-predators that occupy high trophic levels. Despite these species are largely studied, little is known about their diet outside the breeding period. In the present study, we investigated the intra-annual diet of Adélie and Emperor Penguins belonging to five colonies in the Ross Sea through the stable isotope analysis of different tissues (feathers and shell membran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 79 publications
1
4
0
Order By: Relevance
“…The fact that chicks grew up at a similar rate and that breeding success was similar at both localities may also suggest that parents fed their offspring with similar proportions of fish and krill. Suggestively, the summer diet composition reported at AdCo and EdPo in previous years seems to confirm our hypothesis of a similar diet composition in these colonies [65].…”
Section: Discussionsupporting
confidence: 88%
“…The fact that chicks grew up at a similar rate and that breeding success was similar at both localities may also suggest that parents fed their offspring with similar proportions of fish and krill. Suggestively, the summer diet composition reported at AdCo and EdPo in previous years seems to confirm our hypothesis of a similar diet composition in these colonies [65].…”
Section: Discussionsupporting
confidence: 88%
“…When comparing emperor penguin and Adeĺie penguin, basing on stable isotope analysis (Hong et al, 2021), it was found that emperor penguins in the Ross Sea maintain preference for the typology of prey (Antarctic silverfish), while Adeĺie penguin chicks at Cape Hallett versus Terra Nova Bay presented a regional characterization of the diet and an adaptation to prey availability. By contrast, another study, based on isotope analysis, dealing with penguins' diet in the Ross Sea (Jafari et al, 2021) has shown that the relative krill and fish consumption by Adeĺie penguins (Pygoscelis adeliae) and emperor penguins (Aptenodites forsteri) changed in relation to the prey availability, in function of seasonal sea ice dynamics and penguin life cycle phases. Dietary variability of Adeĺie penguin is generally confirmed by the various studies, but it is not always the case for emperor penguin.…”
Section: Discussionmentioning
confidence: 92%
“…In conclusion, it is not surprising that we have not found any relation between krill and emperor penguin, but it could be expected to find it with Adeĺie penguin; a possible reason for not finding any relation could be that we monitored these penguins during phases of active movement to or from feeding areas. Jafari et al (2021) identified in spring and summer an active feeding period for P. adeliae, but we should take into account that duration of foraging trips by these animals could be very different within Antarctic areas (Juaŕes et al, 2016;Olmastroni et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study shows a direct improvement in elephant seal body condition in polynyaforaging animals in the East Antarctic. By inference, polynyas should also provide better foraging for other predators that rely on mesopelagic prey, such as emperor penguins (Aptenodytes forsteri) [62], although this species sometimes favours smaller and ephemeral polynyas, rather than the large, predictable ones [29]. Seals also spent some time outside polynyas (on average 38% of their time), despite polynyas offering a clear advantage in terms of resource availability.…”
Section: Discussionmentioning
confidence: 99%